2006
DOI: 10.1088/0022-3727/39/2/012
|View full text |Cite
|
Sign up to set email alerts
|

RF thermal plasma processing of fullerenes

Abstract: This paper presents results on fullerene formation during the processing of different graphite powders in an RF thermal plasma reactor. Graphite powders of different particle size and purity were fed into the reactor (Aldrich, KS4). Optical emission spectroscopy of atomic and molecular species is used as a diagnostic tool of the RF plasma flame. It was found that rotational and vibrational temperatures of C2 radicals depend on the feed rate of the precursor used. The volumes of RF plasma flame during processin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The methods based on spectral Fourier analysis and approximations in the form of efficient fast fourier transform (FFT) solutions enable obtaining of the spectra of vectors and matrices of red, green and blue (RGB) values for each pixel, which are assigned values in each field. The identical numerical procedure determines the measure of dissimilarities of images whether in the native form or its FFT spectrum [15][16][17][18][19] (Figure 3). …”
Section: Methodsmentioning
confidence: 99%
“…The methods based on spectral Fourier analysis and approximations in the form of efficient fast fourier transform (FFT) solutions enable obtaining of the spectra of vectors and matrices of red, green and blue (RGB) values for each pixel, which are assigned values in each field. The identical numerical procedure determines the measure of dissimilarities of images whether in the native form or its FFT spectrum [15][16][17][18][19] (Figure 3). …”
Section: Methodsmentioning
confidence: 99%
“…Initially suggested by Yoshie et al [53], it consists of the injection of solid carbon particles such as graphite powder or CB. Some plasma technologies are developing this principle, such as 3-phase ac plasma [64,72] or RF thermal plasma [68,70,73]. Todorovic-Markovic et al [68] reported a maximum fullerene yield of 4.1%, a graphite feed rate of 192 g h −1 and a plate power of 27 kW at atmospheric pressure.…”
Section: Fullerenes and Fullerene Sootmentioning
confidence: 99%
“…Recently, it has been demonstrated that large-scale production of fullerenes is feasible by evaporating carbon-containing materials in RF induction thermal plasma reactors [11][12][13][14][15][16][17][18][19] (see Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…Cota-Sanchez et al [15] extensively explored a fullerene synthesis process by an RF plasma jet (2)(3)(4)(5) to investigate the effect of the operating parameters on the fullerene formation, e.g., operating pressure, plate power, and carbon feed rate. Todorovic-Markovic et al reported the dependence of the fullerene yield on the properties of the graphite powder, e.g., mean aggregate size and thermal conductivity, as well as on the helium content in the plasma gas [17][18][19]. In order to investigate the influence of the plasma forming gas and operating pressure on the fullerene synthesis in an RF plasma process, Wang et al [11] developed a two-dimensional (2-D) model without considering the carbon particle injection.…”
Section: Introductionmentioning
confidence: 99%